2019
DOI: 10.1016/j.stem.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Hic1 Defines Quiescent Mesenchymal Progenitor Subpopulations with Distinct Functions and Fates in Skeletal Muscle Regeneration

Abstract: Highlights d Hic1 marks multiple quiescent mesenchymal progenitor (MP) subsets within skeletal muscle d Conditional deletion of Hic1 leads to MP hyperplasia and an activated MP phenotype d Hic1 + MPs generate transit-amplifying progeny post-injury that support regeneration d Following injury, select Hic1 + progeny persist and regenerate the myotendinous junction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
204
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(232 citation statements)
references
References 77 publications
17
204
0
3
Order By: Relevance
“…Two very recent studies have identified a subpopulation of perivascular MSCs in the heart and muscle, which are characterized by the expression of PDGFRα, stem cell antigen-1 (Sca-1, Ly6A) and the tumor repressor hypermethylated in cancer 1 (Hic1) (Scott et al, 2019;Soliman et al, 2020). Both studies have shown that Hic1 + MSCs play important roles in the homeostasis and repair of heart and skeletal muscle, differentiate into different cell types including fibroblasts and are kept in a resting state by Hic1 (Kim and Braun, 2020).…”
Section: A Disrupted Msc Niche Leads To Loss Of Regenerative Potentiamentioning
confidence: 99%
See 2 more Smart Citations
“…Two very recent studies have identified a subpopulation of perivascular MSCs in the heart and muscle, which are characterized by the expression of PDGFRα, stem cell antigen-1 (Sca-1, Ly6A) and the tumor repressor hypermethylated in cancer 1 (Hic1) (Scott et al, 2019;Soliman et al, 2020). Both studies have shown that Hic1 + MSCs play important roles in the homeostasis and repair of heart and skeletal muscle, differentiate into different cell types including fibroblasts and are kept in a resting state by Hic1 (Kim and Braun, 2020).…”
Section: A Disrupted Msc Niche Leads To Loss Of Regenerative Potentiamentioning
confidence: 99%
“…Both studies have shown that Hic1 + MSCs play important roles in the homeostasis and repair of heart and skeletal muscle, differentiate into different cell types including fibroblasts and are kept in a resting state by Hic1 (Kim and Braun, 2020). The transcription repressor Hic1 is required for maintaining quiescence, since deletion of Hic1 leads to activation and expansion of MSCs, and subsequently leads to pathological fibrosis of heart (Soliman et al, 2020) and skeleton muscle (Scott et al, 2019), respectively. The exact molecular targets of Hic1 remain elusive.…”
Section: A Disrupted Msc Niche Leads To Loss Of Regenerative Potentiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the fibrogenic FAPs, we noted a strong enrichment in Periostin (POSTN, Fig S10 F), an extracellular matrix protein acting as a ligand and previously associated with fibrosis and wound healing 48 . More recently, Periostin has been shown to increase in activated FAPs during regeneration in mouse skeletal muscle along with lysyl oxidase enzymes (LOX) 49 . Notably, the lysyl oxidase homolog 4 (LOXL4) was the most differentially expressed gene in our fibrogenic FAPs (Fig S10 F).…”
Section: Increased Reliance On Glycolysis and Lactate Production Is Amentioning
confidence: 99%
“…Here, we sought to explore other cell populations within the skeletal muscle interstitium, containing fibro/adipo progenitors (FAP) and mesenchymal progenitors (MP). These cell populations from the skeletal muscle interstitium are known to support skeletal muscle regeneration and become the source of persistent adipose and fibrotic tissue in pathological conditions such as muscular dystrophy [12][13][14][15][16] . We characterized the skeletal muscle mesenchymal progenitors participating in cartilage and bone formation during bone repair and investigated their function in the context of musculoskeletal trauma.…”
Section: Introductionmentioning
confidence: 99%